Croatia - Living Standards Assessment : Volume 1, Promoting Social Inclusion and Regional Equity - World Bank (Washington, DC, 2012)
The Croatian economy has performed moderately well in the past decade, enabling a gradual narrowing of the income gap with the European Union (EU). Using a cost-of-basic-needs poverty line, poverty in Croatia is found to be low, with only a small proportion of the poor facing hard-core deprivation. Looking ahead, the task of faster external income convergence with the EU will be challenging, and will require both faster job creation as well as flexibility in the allocation of jobs and workers in the economy. These will also help with more rapid improvement in living conditions in lagging regions. To these ends, the report highlights three sets of interrelated policy challenges and priorities: (1) sustaining high rates of growth to permit continued income convergence with Europe; (2) promoting greater labor mobility, including measures aimed at building human capital to improve workers' opportunities; and (3) improving the adequacy and effectiveness of social safety nets within a responsible fiscal framework. In examining regional disparities, several development indicators show that regional disparities in living conditions are significant (though on average no higher than in EU countries), and only partially explained by human capital and other such individual attributes. Building on local comparative advantages offers the best way forward to improve living conditions in lagging regions.